Dilemmas and Governance Strategies in the Implementation of the Modern Apprenticeship System in Chinese Vocational Colleges: A Perspective from Principal-Agent Theory - Dong, Chanjuan; Yang, Wanjie (Journal of Educational Research and Policies, 2024)
As China's industrial economy transitions towards high-quality development, the demand for highly skilled technical personnel has surged. The modern apprenticeship system, an important mechanism for deepening collaboration between educational institutions and enterprises, has been widely promoted within vocational colleges. However, nearly a decade into its implementation, this system faces challenges such as insufficient engagement from enterprises, loose relationships between schools and businesses, and a lack of assessment and feedback mechanisms. These issues have led to suboptimal outcomes in talent development. This paper innovatively applies principal-agent theory to expose conflicts in value demands, adverse selection, and moral hazards within the multifaceted principal-agent relationships among vocational colleges, enterprises, and the government. It proposes governance strategies that involve multi-stakeholder participation in policy-making, the establishment of qualification entry systems for cooperative enterprises, and the improvement of supervision and incentive mechanisms. These strategies aim to resolve conflicts and enhance cooperation efficiency, thereby providing robust support for the effective implementation of the modern apprenticeship system in vocational colleges.